Optimasi Penjadwalan Bimbingan Skripsi Menggunakan Algoritme Genetika (Studi Kasus : Fakultas Ilmu Komputer Universitas Brawijaya) - Lilis Damayanti; Imam Cholisoddin; Marji Marji (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Thesis consultation is an activity that must be done for students who are taking thesis. Usually students who will conduct guidance will meet their lecturer or contact the lecturer before. Because the lecturer also has time to teach and perform other activities related to the campus. The number of students in Fakultas Ilmu Komputer Universitas Brawijaya (FILKOM UB) which they want to do guidance to make the students queue in front of lecturers room while the lecturer has a hectic schedule. Therefore it is necessary for the system to schedule thesis consultation. This research applies the concept of solution obtained using genetic algorithm. Genetic algorithm is a search algorithm that aims to find the optimal solution. The result of genetic parameters obtained in the optimal solution is population size 70, number of generation of 2500, combination of cr and mr value is 0,4 and 0,6. This built system resulted in an optimal thesis guidance schedule with a fitness value of 1,0305.